Homemade Solution of NaOD in D2O: Applications in the Field of Stilbene‐d1 Synthesis. Issue 3 (9th January 2023) - Imai, Keisuke; Tomita, Naohito; Fujioka, Hiroyoshi; Kamiya, Mako; Ogasahara, Riku; Ban, Kazuho; Shimizu, Hyoga; Ishimoto, Takayoshi; Sajiki, Hironao; Akai, Shuji; Sawama, Yoshinari
Abstract: The development of deuterium‐incorporation method is eagerly desired. A solution of sodium deuteroxide in deuterium oxide (NaOD in D2 O) was simply prepared by mixing D2 O and t ‐BuONa. Subsequently, the t ‐BuOD layer, generated under conditions of the salting‐out effect, was separate. The purity (volume of the contaminated t ‐BuOD as side‐product) of the homemade NaOD in D2 O was evaluated by 1 H NMR and Raman analyses. NaOD in D2 O was used for the one‐pot synthesis of mono‐deuterated trans ‐stilbene (stilbene‐ d 1 ) in the aqueous Horner‐Wadsworth‐Emmons reaction. The present method can be widely applied to synthesize the various mono‐deuterated stilbene derivatives with high deuterium content. Additionally, the obtained mono‐deuterated stilbene derivatives could be successfully converted to various deuterated compounds. Abstract : A solution of sodium deuteroxide in deuterium oxide (NaOD in D2 O) was prepared by mixing D2 O and t ‐BuONa. Subsequently, the t ‐BuOD layer, generated under conditions of the salting‐out effect, was separate. NaOD in D2 O was used for the one‐pot synthesis of mono‐deuterated trans ‐stilbene (stilbene‐ d 1 ) in the aqueous Horner‐Wadsworth‐Emmons reaction.